Feasibility Analysis of Straw Mushroom Farming using Cotton Fiber Waste Growth Media in Small Straw Mushroom Businesses (Case in Karangmangu Village, Kramatmulya District, Kuningan Regency, West Java) - Akwan, Muhammad Syamsul; As Shobri, Faral Sahdi; Nugraha, Imam Adi; Sunaryo, Yoyo; Purnomo, Dwi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Merang mushroom (Volvariella volvaceae) grows in rice tangaki (merang) after harvesting (crab). This research aims to find alternative growing media using cotton fiber (industrial waste), in an effort to solve the sustainability of the mushroom business due to the increasingly limited availability of merang. The research was carried out with community groups who are used to trying to grow mushrooms, trying to spread seeds on cotton fibers that have been fermented with yeast bacteria using livestock manure, lime and bran. Through bio-engineering, cotton fiber waste, which was originally a waste material in the furniture industry and yarn spinning, can be used as a medium for growing merang mushrooms. Merang mushroom business actors are able to apply bio-technology engineering appropriately so as to produce merang mushrooms with excellent quality. The results of the economic analysis show that: The average production obtained was 227.21 kg with a revenue of Rp.4,771,500, after deducting production costs of Rp.2,858,928, so the income of merang mushroom farming was obtained of Rp.1,912,571, with an R/C of 1.65. This means that for each victim one unit of cost (Rp.1.00) in the process of merang mushroom farming will be obtained 1.65 units (Rp.1.65).